The Influence of CSR, Environmental Awareness and Audit Committee Quality on Company Earnings Quality - Amelya Amelya; Shinta Ningtiyas Nazar (Information Technology and Science (ITScience), 2022)
This study aims to examine the effect of Corporate Social Responsibility (CSR), environmental awareness and audit committee quality on earnings quality. The research methods used are quantitative research methods and associative methods. The population in this study is the Sri Kehati Index company listed on the Indonesia Stock Exchange for the 2016-2020 research period, totaling 25 companies, from the total population a purposive sampling technique is used with several criteria to determine the sample, so that a sample of 8 companies is obtained. The data analysis technique used in this study uses eviews10 which includes descriptive statistical tests, panel data model analysis, classical assumption tests and hypothesis testing. The results of this study indicate that partially corporate social responsibility (CSR) is considered to have an effect on the Earning Quality of Sri Kehati Index companies listed on the Indonesia Stock Exchange for the 2016-2020 period, while environmental awareness and audit committee quality are considered to have no effect on the Earnings Quality of Sri Kehati Index companies. Sri Kehati listed on the Indonesia Stock Exchange for the period 2016-2020. The results of this study also show that simultaneously the three independent variables, namely Corporate Social Responsibility (CSR), Environmental Awareness and the Audit Committee, do not have a significant influence on the dependent variable of Earnings Quality.